Analysis of silica and silicon carbide abrasives characteristics on denim wear. Issue 11 (3rd September 2022) - Elaissi, Arwa; Ghith, Adel; Alibi, Hamza
Abstract: This paper presents the development of certain abrasives based on selected industrial wastes and gives an idea of their postuse behavior. These abrasives are manufactured using two methods: pulverization and coating. For these purposes, we used cellulosic nonwoven fibers as reinforcement, three types of resin (polyurethane, acrylic, and polyester) as a matrix, and abrasive grains of silicon carbide (SiC) and silica to obtain the abrasive character. We report the wear of the developed materials by abrasion, the evaluation of their roughness, the influence of the type of the abrasive grains, and their sizes on the wear performances. Scanning electron microscopy was performed to show the morphology of abrasives. The weight loss of abrasives was measured by thermogravimetric analysis and its derivative. Fourier‐transform infrared spectroscopy allows the chemical characterization and identification of abrasive grains. Under the same test conditions, experimental results indicate that silica‐based abrasives exhibit higher surface roughness and abrasion wear rate than SiC‐based abrasives. Abstract : The materials used for the manufacture of abrasives.